2006
DOI: 10.1093/aje/kwj254
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Brain Tumors Associated with Exposure to Exogenous Female Sex Hormones

Abstract: The etiology of brain tumors is largely unknown. Prior observations have implicated gender-specific hormones in the pathogenesis of these tumors. In a population-based case-control study, the authors identified all women aged 20-69 years who had been diagnosed with meningioma or glioma during 2000-2002 in four regions of Sweden. Controls were randomly selected from the study base. Detailed information on hormone usage, including use of hormonal contraceptives, hormonal treatment for gynecologic problems, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 44 publications
12
127
3
3
Order By: Relevance
“…In addition, as in this study, previous studies have found no association between oral contraceptive use and meningioma or glioma risk (Jhawar et al, 2003;Custer et al, 2006;Wigertz et al, 2006).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, as in this study, previous studies have found no association between oral contraceptive use and meningioma or glioma risk (Jhawar et al, 2003;Custer et al, 2006;Wigertz et al, 2006).…”
Section: Discussionsupporting
confidence: 65%
“…A number of different issues were covered by detailed questions, including questions related to reproductive history. Results on exogenous female sex hormones and brain tumor risk have previously been reported for the Swedish data (14). The age range for inclusion differed slightly between the countries: ages 20 to 69 y in the Nordic countries and ages 18 to 59 y in the United Kingdom.…”
Section: Methodsmentioning
confidence: 80%
“…Progesterone, estrogen, and androgen receptors are expressed in meningiomas (7)(8)(9) and gliomas (10,11) in various degrees. Use of exogenous female sex hormones has been reported in relation to meningioma and glioma risk with inconsistent results (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The risk of meningioma is increased among postmenopausal women who have used hormonal treatment replacement therapy and among women who have used longacting contraceptives. 7 The suspicion that high daily doses of cyproterone acetate for long periods could be responsible for the development of meningiomas, and especially multiple meningiomas, was reported in 2008. 1 Froelich et al 1 reported multiple meningiomas in 9 female patients treated with cyproterone acetate.…”
Section: Discussionmentioning
confidence: 99%